2010
DOI: 10.1007/s11033-010-0072-8
|View full text |Cite
|
Sign up to set email alerts
|

An MspI polymorphism in the inhibin alpha gene and its associations with superovulation traits in Chinese Holstein cows

Abstract: To identify a predictor to forecast superovulation response on the basis of associations between superovulation performance and gene polymorphism, the PCR-RFLP method was applied to detect an A>G transition determining an MspI polymorphism at position 192 in the exon I of the bovine inhibin alpha (INHA) gene and evaluate its associations with superovulatory response in 118 Chinese Holstein cows treated for superovulation. Association analysis showed that cows with the GG genotype resulted in a significant incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
0
19
1
7
Order By: Relevance
“…Furthermore, three of the SNP were found to be expressed within the ovary (Table 3). In particularly, INHA (inhibin alpha) which has various polymorphisms associated with Holstein cow response to superovulation and is well known for its role in regulating follicle stimulating hormone secretion [78]. This gene was also reported in the GWAS-gene identification efforts of Fortes et al [11].…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, three of the SNP were found to be expressed within the ovary (Table 3). In particularly, INHA (inhibin alpha) which has various polymorphisms associated with Holstein cow response to superovulation and is well known for its role in regulating follicle stimulating hormone secretion [78]. This gene was also reported in the GWAS-gene identification efforts of Fortes et al [11].…”
Section: Resultsmentioning
confidence: 96%
“…The injections were given at 12-h intervals in a dose step-down manner -i.e., doses of 5.4, 4.4, 3.4, and 2.4 mL on each day -as described in previous studies (Tang et al, 2011). Each cow was twice given 4 mL 0.15 mg/mL prostaglandin F2α (Qilu Animal Health Products Co., Ltd., China) along with the sixth and seventh FSH treatments.…”
Section: Superovulation Procedures and Embryos Harvestmentioning
confidence: 99%
“…Genomic DNA was obtained from blood samples by the method of modified Salting out, described by Miller and coworkers (Miller et al, 1988). To amplify a fragment of 249pb on the INHA exon 1 which contains one reported SNP of A192G (GenBank number: rs41257116) were used the primers F: 5'-GCCCTGTTTCTGGAT-GCC-3' and R: 5'-ATTCAACCCAACCTGCCTA-3' (Tang et al, 2011). The PCR was performed in a final reaction volume of 30 µl, containing 3.8 µl 10X reaction buffer (200 nM (NH 4 ) 2 SO 4, 750 mM Tris-HCl pH 8.8 at 25 °C), 2.5 mM of Mg Cl 2 , 15 pmol of both primers, 0.4 mM of dNTP (deoxyribo nucleotide triphosphate), 1.5 unit of Taq-DNA polymerase (Thermo Scientific) and 100 ng of genomic DNA as template.…”
Section: Dna Extraction and Genotyping By Pcr-rflpmentioning
confidence: 99%
“…In cattle has been reported a change of an adenine for a guanine at position 192 (A192G) on the exon 2 of the INHA, this SNP is considered as a synonymous mutation, this means that the change of an adenine for a guanine does not change the amino acid sequence of the protein, since both codons (CGA and CGG) encode the amino acid Arginine (NCBI, 2013), but result in an additional restriction site for the enzyme MspI. In Chinese Holstein cattle has been found that this SNP is associated with response to superovulatory treatments (Tang et al, 2011) and semen quality (Sang et al, 2011), and the G allele exert a positive effect in both characteristics. However there are no studies about the effect of this polymorphism on the main parameters of zootechnical interest.…”
Section: Introductionmentioning
confidence: 99%